Sistem Penjaminan Mutu Internal (SPMI) pada Program Studi Pendidikan Agama Islam IAINU Kebumen - Agus Salim Chamidi; Rita Sulastini; Sri Handayani (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2021)
This research article aims to get an overview and analysis of the internal quality assurance system (SPMI) in universities. The research was conducted at the Islamic Religious Education Study Program (Prodi PAI) IAINU Kebumen in October-December 2021. The research was qualitative in nature using interviews, observation, and documentation methods. Documentation related to the SPMI PAI Study Program IAINU Kebumen document, interviews with a number of related officials/lecturers, and observations related to the things needed. The results of the research show that the SPMI PAI IAINU Kebumen Study Program has been going well in accordance with applicable standards. There are regular improvement efforts. Recommendations, the need to oversee the revision of a number of guidelines.